Fundamental of Entrepreneurship ENT 300 : Shinezia Company (An ideal bathroom for home) / Amal Amilla Sahat... [et al.] - Sahat, Amal Amilla; Bungan, Wenni Bulan; Jackson, Jazlina Jenna; Abdul Hai, Nurul Hidayah; Mohd Khairul, Ajlaa Athirah (2012)
The name of our company is ShineZia Company. The business is in form of enterprise which consists of five members. Each partner contributes certain amount of capital as agreed in agreement. The main business activity is providing renovation and decoration for the bathrooms with technologically advance equipment’s that may attract customers in designing their dream bathrooms.